Youth Gang Members: Psychiatric Disorders and Substance Use - Albert John Sargent; Sherri Simpson; Dennis W. Young; Amy Mayhew; Ayanna Brown; Stephanie Kwok; Matthew Shelton; Barbara Robles; Toi Blakley Harris; Sara Elkins; Ashley Butler (Laws, 2013)
Objective: Approximately 260,000 of youth in the United States are gang-affiliated. There is a paucity of data available to identify the prevalence of mental health disorders in this population. Gang members share many of the features of “at risk” or juvenile justice involved youth who deny gang membership. The authors identified rates of psychiatric disorders within a juvenile justice population delineated in three categories: gang members, friends of gang members, and non-gang members. Methods: A retrospective review of records obtained by a juvenile probation department. A large detention center conducted mental health screenings on 7,615 youth aged 13–17. The mental health screenings were performed by either a master level or doctoral level mental health professional. Odds ratios were computed as an effect size for gender, race/ethnic differences, and gang-membership associations with self-reported psychiatric and substance use disorders. Logistic regression was used to evaluate the risk for psychiatric and substance use disorders among gang-members and friends of gang members. Diagnostic information was generated through a clinical interview and flexible battery. Results: Of the 7,615 youth in this study, ~50% had contact with gangs; 11% were self-identified gang-members, and 38% acknowledged having at least one friendship with a gang member. Similar to other studies, being male was a risk-factor for gang-membership (2.31 odds). In this multi-racial and ethnic study, Latinos had a greater affiliation with gang membership and association with gang members as friends (1.44 odds). Gang members were found to have increased rates of post-traumatic stress disorder (1.77 odds), current substance abuse (2.58 odds), oppositional defiant disorder, (1.24 odds) and conduct disorder (4.05 odds); however, they were less likely to have an adjustment disorder than non-gang members (0.70 odds). Conclusions: Juveniles who received a mental health assessment in this study were found to have differences in rates of psychiatric disorders and substance use based upon gang-affiliation or association. Current data is limited and inconsistent in the delineation of individual, family, peer, school and community characteristics specific to gang members. These differences warrant further investigation for intervention and treatment.